Text and binary data transfer using postfix and UUCP over an HF radio link. - Cabeza, Ivy
This paper discusses the first ever implementation of UNIX-TO-UNIX COPY (UUCP) and POSTFIX over an HF radio network. It allows reliable text and binary data transfer between computer terminals several hundreds of kilometers apart. The system was developed for use by PAGASA (Philippine Atmospheric, Geophysical and Astronomical Services Administration) for collection of weather data from remote weather stations distributed around the country to a central server located in Diliman, Quezon City.